Pediatric pancreatitis: Outcomes and current understanding - Deepti Vepakomma (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this study was to analyze the clinical spectrum of pediatric pancreatitis and review current literature with regard to concepts of disease and management approaches. Materials and Methods: This is a retrospective analysis of pancreatitis patients admitted to a tertiary referral pediatric surgical unit from March 2013 to September 2018. Results: There were 106 patients from 1 year to 18 years with median age group between 11 and 15 years and equal gender distribution. Sixty-two children had acute pancreatitis (AP), with 13 of them having recurrent episodes. Forty-four patients had chronic pancreatitis (CP). Definite etiology was found in 11 AP patients. All patients had radiological changes. All AP patients were treated symptomatically except those with correctable underlying etiology. Sixteen with CP required intervention in the form of endoscopic retrograde cholangiopancreatography sphincterotomy/stenting or surgery. There were two mortalities. One with acute necrotizing pancreatitis and one CP girl due to the complication of diabetes mellitus, unrelated to episode of pancreatitis. All others are well at the last follow-up. Conclusion: Pediatric pancreatitis is a disease with a wide spectrum, but management can be standardized. Newer studies reveal that certain genetic mutations make children more susceptible to pancreatitis. Increasing incidence must prompt us to evaluate further so as to better equip ourselves to managing this disease entity in all its forms and evolve preventive strategies.